Surface breakdown property of SiO2 added MgO under electron bombardment in vacuum: a promising materials for spacecraft and space station - Sutjipto, Agus Geter Edy (SENTRA Academic Publishers, 2007)
A surface breakdown (flashover) might occur on the surface of an insulator when it was bombarded by electron beam until exceeding a critical value. The strength of SiO2 added MgO to withstand flashover treeing appearance was evaluated by bombarding the samples by 25 keV electron beam generated by a scanning electron microscope. There was a significant increase of bombardment-time to initiate surface breakdown when SiO2 addition was 6 wt%. This compound was about 5 times better in withstanding breakdown compared with materials commonly used in spacecraft such as teflon, kapton and milar materials. It could be considered that 6 wt% SiO2 added MgO became a promising material for spacecraft and space station where space radiation may damage spacecraft body or influence the communication system.